2013
DOI: 10.7566/jpsjs.82sa.sa002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Butyl- and Hexyl-Methylimidazolium Bromide Ionic Liquids

Abstract: We have carried out quasi-elastic neutron scattering measurements, supported by classical molecular dynamics simulations, to determine the liquid state dynamics of 1-butyl-3-methylimidazolium bromide and 1-hexyl-3-methylimidazolium bromide. The spectra are fitted with two-and three-Lorentzian models and indicate the existence of a localized dynamics of the alkyl chains in the sub-picosecond range. The spatial dependence of the dynamics is consistent with a confined translational diffusion model with parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…[10][11][12][13] Additionally, QENS allows one to obtain spacial characteristics of observed processes, such as radii of confinement, correlation lengths or jump distances, because typical wavelengths of incident neutrons are of the order of interatomic distances in solids and liquids. Being particularly sensitive to hydrogen atoms, incoherent neutron spectroscopy is beneficial in investigating dynamical processes in hydrogen-rich materials, to which ILs can be ascribed as well, [14][15][16][17] and finally could be applied to obtain information on proton diffusivity in PILs. 18,19 The objective of our work was to employ QENS and deuterium labelling to explore transport properties in triethylammonium triflate (TEA-TF).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Additionally, QENS allows one to obtain spacial characteristics of observed processes, such as radii of confinement, correlation lengths or jump distances, because typical wavelengths of incident neutrons are of the order of interatomic distances in solids and liquids. Being particularly sensitive to hydrogen atoms, incoherent neutron spectroscopy is beneficial in investigating dynamical processes in hydrogen-rich materials, to which ILs can be ascribed as well, [14][15][16][17] and finally could be applied to obtain information on proton diffusivity in PILs. 18,19 The objective of our work was to employ QENS and deuterium labelling to explore transport properties in triethylammonium triflate (TEA-TF).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of CnmimX are also investigated mainly in the context of the non-Stokes-Einstein relation which makes a connection between the microscopic and macroscopic dynamics. Microscopic motions have been investigated by nuclear magnetic resonance (NMR), [46][47][48][49][50][51] quasielastic neutron scattering (QENS), and inelastic x-ray scattering measurements, 8,13,15,[52][53][54][55][56][57][58][59][60][61][62][63] while macroscopically by viscoelastic, 16,46,47,55,58,62,[64][65][66][67][68][69][70][71] dielectric, 49,50,55,[71][72][73][74][75][76][77] and ionic conductivity measurements. 46,47,68,…”
Section: Introductionmentioning
confidence: 99%
“…40 kJ mol −1 . 15 The several incoherent QENS studies 8,[52][53][54]56,57,59,61,62 on hydrogenated CnmimX (n < 10) presented the relaxation of the alkylchains with τ of the order of ps and a small ∆E a (ca. 5 kJ mol −1 ) and that of the ionic diffusion with intermediate τ and ∆E a .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] These alternations are now known to be fingerprinted by well-defined X-ray and/or neutron scattering 13,[21][22][23][24] features in the low momentum transfer (Q) range. The interest toward this feature is witnessed by the wealth of studies addressing its nature and dependence upon chemical nature of the ions, [25][26][27][28][29][30] temperature, 13,15,31 mixture composition, [32][33][34][35][36][37][38][39][40][41] and, only recently, pressure. [42][43][44][45] High pressure studies are an important tool to explore the details of microscopic and mesoscopic correlations in complex materials.…”
mentioning
confidence: 99%
“…Pressure changes allow investigating intermolecular interactions, by inducing density changes without introducing the chaotic perturbation that temperature changes induce. As a matter of fact, while temperature dependence studies of morphology in RTILs have been reported in the past, 13,15,31 the pressure dependence of the mesoscopic organization in aprotic RTILs has been explored by means of experimental X-ray studies [42][43][44] and simulations [45][46][47][48][49][50] 42 Therein the progressive position shift and amplitude vanishing of the low Q peak centred at ca. 3 nm −1 had been observed.…”
mentioning
confidence: 99%